Hubungan Faktor Internal dan Eksternal terhadap Proses Pengambilan Keputusan Etis - Niluh Putu Dian Rosalina Handayani Narsa; Kadek Pranetha Prananjaya (Journal of Accounting and Investment, 2017)
This study aims to examine the relationship of two factors, namely internal factors (based on the individual characteristics: personal moral philosophy which is consisting of idealism and relativism, education level, gender and age) as well as external factors (moral intensity which has six variables, namely the magnitude of the consequences, social consensus, probability of effect, temporal immediacy, concentration of effect, and proximity) to the three-stage of ethical decision-making processes (ethical recognition, judgment and intention). Data collected used survey method. Respondents are undergraduate and graduate students of accounting. A total of 173 respondents had fill out questionnaires completely. Analyis data used hierarchical linear regression, independent t-test and one-way anova. The findings show that some of the variables tested had a significant relationship as predicted in all of the three stage of ethical decision-making processes with a difference in level of significance. However, no significant relationship was found regarding the relationship of age in all of the three stages, as well as the the evidence of a significant relationship that is inconsistent with the predictions regarding the relationship of gender in the stages of ethical intention and the relationship of probability of effect and proximity in the stages of ethical recognition.